A stormy chase of coronary artery spasm : Thyroid storm in acute myocardial infarction - Ho Yik, Hon; Caryn Tsujean, Lim; Chow Han, Bing; Chan Pei, Lin; Tan Chen, Ting; Asri, Said (Medical Journal of Malaysia Case Reports (MJM Case Reports), 2022)
SUMMARY Cardiovascular disease represents the largest cause of death globally, with multifactorial causes. This is a case study of a thyroid storm with hyperactive coronary arteries resulting in acute myocardial infarction (AMI). A 56-year-old gentleman presented with left-sided chest pain radiating to the neck. Initial ECG showed ST elevation over anterior leads, which dynamically changed to Lambda-wave (“shark fin” pattern) over inferior leads 60 minutes later, along with raised cardiac enzymes. Urgent invasive coronary angiogram was performed, in which we repeatedly did ballooning of the left anterior descending coronary artery due to recurrent spasms in the artery, with the patient’s haemodynamics being labile with systolic blood pressure of as low as 60 mmHg. He was intubated for acute pulmonary oedema and admitted to cardiac intensive care unit postprocedure and had persistent tachycardia with multiple episodes of tachyarrhythmia. Laboratory test revealed hyperthyroidism, and he was treated for thyroid storm with Burch-Wartofsky Point Scale of 50 points. However, his clinical condition deteriorated rapidly with the development of acute kidney injury and severe metabolic acidosis. He eventually succumbed after 4 days of intensive care despite maximum multidisciplinary resuscitation effort. This study calls for routine screening of thyroid function test in patients with persistent tachycardia during AMI.